The Implementation of Emotionally-Valuable Component of the Content of Foreign-Language Education (on the Mate rial of Study Course "Spotlight"). Part I - M. N. Tatarinova; O. V. Sungurova (Russian State Vocational Pedagogical University, 2019)
Introduction. The revaluation of the tasks and results of school foreign-language education in our country updated the role of the emotionally-val- uable component (EVC) of the content of foreign-language courses. There is broad agreement that the compliance of its criteria today is the most important prerequisite of foreign languages viability.The aim of this article is to provide a scientific answer to the question if there is necessary background for the implementation of the EVC of the content of foreign-language education in the current study course "Spotlight".Methodology and research methods. As the fundamental methodological tool the emotionally-valuable (axiological) approach to the study was applied. A number of complementary methods were used: a theoretical systemic-structural and comparative analysis; an analytical experiment - the content-analysis of the current English- language study course for a secondary school; a constructive (creative) experiment (experiential learning); a method and principles of visibility (a tabular and graphical presentation of information); methods of mathematical statistics.Results and scientific novelty. It is proved that the EVC in the linear structure of the school subject "A foreign-language" is able to ensure an integral formation of a student's personality with developed intellectual, volitional and emoti- onally-valuable spheres. A practical implementation of this component is possible through students' work with speech patterns of emotionally-valuable context. The indicators of emotional value of teaching materials are selected. The content- analysis of the text library of the study course "Spotlight" showed that it does not fully meet the requirements for super-phrasal units of the EVC, intended to maintain an appropriate level of language skills and encourage the acquisition of various kinds of foreign-language speech activities: speaking, listening, reading and written speech. Therefore, additional adjustment of a number of speech samples is required in order to create all the necessary background for the exploitation of the EVC of the school programme content at different stages of foreign-language training. The results of experiential learning a foreign language, involving carefully selected texts of a sufficient and high degree of emotional value, and the use by teachers of special techniques of work, adequate to the axiological potential of speech samples, prove the appropriateness of such an approach to the organisation of an educational process. The axiological orientation of the training content significantly improves students' speech activities and contributes to the development of their emotionally-valuable relations with the surrounding world.Practical significance. The materials in this publication may be in demand when making constructive changes and additions to the content and technologies of school foreign-language education.